Draft Annual Plan 1976-77 Volume I General Government of Jammu and Kashmir - Planning Commission (Planning Commission, 1975)
The Plan Outlay for 1975-76 was approved at Rs.53.75 Crores constituting 16% of the outlay for the 5th Plan period. During the course of the year, the State Government allowed step up in some priority sectors in order to ensure that no Worthily scheme/project is starved for funds. The step up was allowed in the Case of Education, Health and Economic Services.
Department of Planning and Development, Government of Jammu and Kashmir